When a harmless procedure causes a life‐threatening problem: a case report of metformin‐associated lactic acidosis following a colonoscopy. (13th February 2019) - Pessoa, Ana; Quintela, José; Tavares, Sofia; Marques, Marta; Pereira, Joana; Silva, Duarte; Pimentel, Rodrigo; Pereira, José Manuel
Abstract : Metformin is the preferred initial pharmacologic agent for the treatment of adults with type 2 diabetes mellitus. Although considered safe, it carries a potential life‐threatening risk of lactic acidosis. Metformin‐associated lactic acidosis is believed to be a consequence of metformin inhibition of the mitochondrial respiratory chain, and has a mortality ranging between 10–50%. However, its outcome is better than lactic acidosis of other cause with similarly severe acid‐base imbalance. In this article, we describe the case of a 72‐year‐old woman with type 2 diabetes mellitus, presenting to the emergency department with gastrointestinal symptoms associated with severe lactic acidosis (arterial pH 6.6 and lactate 17mmol/L) and acute kidney injury. Upon obtaining collateral history, the diagnosis of severe metformin‐associated lactic acidosis following a colonoscopy preparation was made. The patient was admitted to the intensive care unit for organ support, being ultimately discharged home after one month in hospital. At discharge, she had full neurologic recovery, improvement of renal dysfunction and was under glycaemic control with insulin therapy. Metformin‐associated lactic acidosis' mortality rate is about half that of the mortality rate seen in individuals with lactic acidosis of other cause. Despite current therapies being effective, preventive measures should always be primal. It is important to educate patients to discontinue this medication when appropriate and keep hydrated. Both upper and lower endoscopies should not be undertaken during the same day, as this further worsens dehydration. Other medications capable of impairing renal function should also be reviewed. Copyright ©